TEKNIK PEMBUATAN BIBLIOTHERAPY - Syamsudin, Syamsudin; Iswanti, Sri (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
The   community     service    held   the   Department    of   Educational Psychology   and  Guidance,   State  University   of  Yogyakarta   has  two  aims. First,   Junior  High  School  Teacher  of Guidance  have knowledge   and  skills about Bibliotherapy.   Second,  the teachers  of guidance  in Junior  High School have high motivation  to develop  bibliotherapy    so that they can make  a bank of Bibliotherapy  in MGP  (Teacher  of Guidance  Deliberation  Forum).This  training   has  three  methods.   First,  exchange   ideas  to  find  the problems  in guidance  and counseling   faced by Junior  High School  teachers of   guidance   in   Bantul   Regency.    Second,   talks   and   discussions    about bibliotherapy     including     their    management     and    development.     Third, discussion  and training  of making  bibliotherapy.The   success   of  this   training   was   indicated   by  the   increase    ofknowledge   on   making   the   bibliotherapy    and   the   gathering   of   62   exp bibliotherapy  managed  by the Junior High School Teachers of Guidance Deliberation  Forum  in Educational   Department  in Bantul Regency.Key words: Training, bibliotherapy, guidance and counseling